Audit firm transparency disclosures and audit quality. Issue 2 (28th April 2021) - Johl, Shireenjit K; Muttakin, Mohammad Badrul; Mihret, Dessalegn Getie; Cheung, Samuel; Gioffre, Nathan
Abstract : This study examines whether audit firm transparency disclosures are associated with audit quality and explores the effect of audit firm size on this association. Using control and treatment samples of Australian audit firms pre‐ and post‐introduction of a disclosure requirement, we document that firms affected by the regulation display improvement in audit quality. We find that the extent of transparency disclosures is positively associated with audit quality, and audit firm size affects this association in a non‐linear manner. That is, the association is stronger for large non‐Big 4 than Big 4 firms and insignificant for medium and small non‐Big 4 firms. The results suggest that large non‐Big 4 firms (and Big 4 to a lesser extent) attempt to distinguish themselves through audit quality by providing extensive disclosures about their systems and practices. The incremental effect for Big 4 firms is smaller, as these firms have an already established reputation for quality in the audit market.